Remote sensing of the Himalaya - Kawosa, M. A. (Dehra Dun : Natraj Publishers, 1988)
Remote Sensing, No longer a novel technology, has served now for survey and mapping of natural resources for a great many years and in india for at least a decad. In india its principal and most useful applicatiopns have been in the identification of vegetation in tha mapping of surfave geological structures and the ground water exploration. This book presents in its earlier chapter much introductory material on the principles of remore sensing and contains descriptions of image interpratation methods. The later chapters discuss the techniques of computiontion and evaluation and also the application of the data for resource management.
Includes bibliography
Keywords: Himalaya Mountains -- Remote sensing; Remote sensing; Himalaya Mountains